The Perils of Single‐Site Genetic Testing for Hereditary Cancer Syndromes in the Era of Next‐Generation Sequencing. (14th February 2018) - Casasanta, Nicole; Stark, Elizabeth; McHenry, Allison; Biagi, Tara; Kaltman, Rebecca
Abstract : : A challenge in counseling patients with a family history suggesting a hereditary cancer syndrome is deciding which genetic tests or panels to order. In this article, we discuss the identification of multiple familial mutations through genetic counseling and panel testing. For patients meeting National Comprehensive Cancer Network criteria for clinical genetic testing, providers should consider expanded panels to provide a more complete assessment of one's genetic risk. The continued use of expanded panel testing in the clinical setting will help inform optimal management of cancer patients, as well as the management of their unaffected family members. The mutation discovered in this case was in the ATM gene. The clinical significance of the mutation, potential therapeutic targets, and proper clinical management are discussed. Key Points : With single‐site genetic testing, there is the potential to miss hereditary genetic syndromes that can be managed clinically. Between 4% and 6% of hereditary breast and ovarian cancer syndromes are caused by genes other than BRCA1 and BRCA2 . ATM is a DNA mismatch repair gene associated with double‐stranded DNA break repair and cell cycle checkpoint arrest. The risk of developing female breast cancer by age 50 and by age 80 in ATM heterozygotes is 9% and 17%–52%, respectively. Abstract : A challenge in counseling patients with a family history of hereditary cancer syndrome is deciding which genetic tests or panels to order. In some cases, expanded panels should be considered to provide a more complete assessment of a patient's genetic risk. The mutation discovered in the case reported in this article was in the ATM gene. The clinical significance of the mutation, potential therapeutic targets, and proper clinical management are discussed.